Roles of the teacher for increasing learning quality of students - Winda Erlia (ETUDE: Journal of Educational Research, 2021)
Background: Understanding the role of teachers in improving the quality of student learning and knowing that students even though using e-learning can learn effectively or not and can improve the quality of student learning, even though they do not learn face-to-face or directly but the teacher must be able to know the ability of students to master and understand this learning and students get maximum and effective learning from the teacher because the teacher is an educator. In this education, especially in e-learning, teachers or educators do not provide maximum learning or are less effective in E-learning. Purpose: In order to know the teacher's perspective on improving the quality of student learning in E-learning. Design and methods: This type of research uses the case study method, data sources: documents and interviews using a qualitative approach. The research subjects were 6 elementary school teacher respondents. Data validation used inter-researcher triangulation. Results: the results of this study show that there are various kinds of teacher roles that are very important in improving the quality of student learning, even though e-learning is less effective in improving the quality of student learning.